A Needs Analysis of English for Graphic Design Students: A Case Study at Vocation High School - Yulin Rabaiya; Nurlaila Husain; Haris Danial (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study aims to analyze the English learning needs of graphic design students at SMK Negeri 1 Dungaliyo, focusing on target needs and learning needs within the framework of English for Specific Purposes (ESP). This research employed a mixed methods design with an exploratory sequential approach. Quantitative data were collected through questionnaires, while qualitative data were obtained through semi-structured interviews and classroom observations. The findings reveal that students need English primarily for professional communication, understanding design-related materials, and presenting their work. However, current learning practices still emphasize General English rather than ESP-based instruction. Students also face challenges such as limited mastery of technical vocabulary, low confidence in speaking, and lack of contextual learning materials. In addition, teaching strategies are still dominated by teacher-centered methods with limited use of interactive and contextual approaches. Therefore, this study suggests the need to develop English learning materials and strategies that are more relevant to the field of graphic design to better support students’ academic and professional needs.